Development of an advanced gaseous neutron imaging system based on thick gas electron multipliers with 2d delay line readout - Burke, Devin (My University, 2021)
Neutron imaging is a non-destructive technique with many applications in diverse fields such as industrial quality assurance, archaeology, and border security. However with the high cost of the standard fill gas 3He and the high cost of scaling conventional digital imaging systems to large areas its applications are limited. Here is presented the proof of concept for a gaseous neutron imaging system utilizing a 10B4C solid state converter and THGEM technology and 2D passive delay line readout. THGEMs used for signal amplification can be produced cost effectively and in large areas by PCB manufacturers. This combined with the reduced channel processing requirements of delay lines over individual pixel readouts results in a cost-effective and scalable system when compared to similar designs using solid state multipliers such as silicon photomultipliers. Here is presented a proof of concept of this imaging system with data acquisition accomplished by digitization and offline image reconstruction achieving mean X and Y resolution of = (1.37+-0.24) mm and = (1.15+-0.13) mm respectively. Studied in parallel with this system is the effectiveness of gadolinium oxide based paint as a thermal neutron shield and image contrast agent.
THGEM based neutron imaging system
Keywords: neutron; imaging; thgem; mpgd; boron; proportional counter; delay line